In vitro Antimicrobial Activity of Hexane: Petroleum Ether Extracts from Fruits of Momordica charantia L. - Yap, WaiSum (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTIn the present study, the antimicrobial activity from fruit extract of Momordica charantia L. using combination of hexane and petroleum ether at different concentrations (0%, 20%, 40%, 60%, 80% and 100%) was assessed and tested against four Gram-positive bacteria (Bacillus cereus, Bacillus subtilis, Enterococcus faecalis and Staphylococcus aureus), four Gram-negative bacteria (Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Serratia sp.) and a fungus (Candida albicans). Among the four Gram-positive bacteria tested, Bacillus cereus was found to be the most susceptible bacteria with the percentage inhibition of 109.5 ± 3.69% at 100% hexane (1mg/ml). Nevertheless, Klebsiella pneumonia was found to be the most susceptible Gram-negative bacteria with the percentage inhibition of 125.0 ± 5.27% using 40% hexane while the fungus Candida albicans demonstrated maximum inhibition with a percentage inhibition of 297.2 ± 6.80% using 100% hexane. Thus, the in vitro study of hexane : petroleum ether fruit extract of Momordica charantia L. has shown its potency as a promising antimicrobial agent towards a broad range of pathogenic microorganisms tested.